GREENBUG RESISTANCE IN OAT ACCESSIONS FROM DAGESTAN AND CAUCASIAN COUNTRIES - E. E. Radchenko; M. A. Chumakov; I. G. Loskutov (Труды по прикладной ботанике, генетике и селекции)
Background. The breeding of resistant varieties is an effective way to control greenbug Schizaphis graminum Rondani, an economically important pest of oat and other cereals in southern Russia. The insect-host differential interaction necessitates a constant search for new resistance donors.Materials and methods. One hundred and ninety one accessions (mostly landraces) from the Caucasian countries (Armenia, Azerbaijan and Georgia) as well as from the North Caucasus of the Russian Federation (Dagestan) were assessed for greenbug resistance. The Krasnodar (Gulkevichi District) insect population was used in the experiments. The intact plants were uniformly infested with differentaged aphids in the phase of two leaves by shaking insects onto them. When the susceptible control (cv. Borrus) died, the plant damage score was determined using the scale from 0 (no damage) to 10 (91–100% of the leaf surface damaged, plant’s death). The plants with the score of 1–4 points were classified as resistant, 5–8 moderately resistant, and 9–10 susceptible.Results and conclusions. A local oat accession from Georgia (k-4308) was noted for its high insect resistance. Also, heterogeneity of the studied trait was demonstrated by 38 oats forms, most of which were differentiated into two phenotypic classes, and a wide range of plant damage variation was characteristic of 16 accessions. The specific occurrence of resistant forms was the highest among oat landraces from Azerbaijan: two out of five studied accessions (40%) carry resistance genes with a distinct phenotypic manifestation. They are followed by accessions from Georgia (25%), Armenia (17.3%) and Dagestan (13.8%). After selection for resistance, the identified forms can be used in plant breeding.